Entangled between tradition and modernity: the experiences of Bhutanese working women - Dayaram, Kandy; Pick, David (Emerald Group Publishing Limited, 2012)
Purpose – The purpose of this article is to examine the shifting roles of Bhutanese women in employment and family as they navigate tensions between tradition and modernity. Design/methodology/approach – To achieve greater understanding of the experiences of the women in this research, a theoretical framework dubbed a “matrix of entanglements” is developed and tested through the analysis of qualitative interview data from 38 Bhutanese working women. In doing so the ways in which these women reconcile competing demands on their personal resources are assessed. Findings – It is found that the women are experiencing entanglements as they negotiate western endogenous modernity, an emerging “Bhutanese modernity”, and traditional social, cultural, economic and political patterns.